Cold response of annual Mediterranean pasture legumes - Hekneby M.; Antolín M.C.; Sánchez-Díaz M. (Quality in lucerne and medics for animal production, 2001)
In southern Europe, the trend towards low input agriculture gives new incentives to sow forages, legumes in particular, with the aim of improving natural pastures, increase the quality of animal feeding and improve soil fertility. However, growth of forage crops in these areas is seriously limited by the ability of each species to grow during cold winters. Therefore, the objective of this work was to evaluate several annual medics cultivated in Mediterranean zones for cold response. Annual species tested were Medicago polymorpha L., M. truncatula Gaertn, M. rugosa Desr. and M. scutellata (L.) Mill. Twenty day old plants were subjected to two temperature regimes: 20-15 degrees C or 10-5 degrees C (d-n) for 40 d. Leaf area, dry matter production, growth parameters and solute content (proline, starch and total soluble sugars) were determined. Results will be discussed in relation to differential response of annual medics to cold conditions.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)